Komparasi Hasil Belajar Matematika Siswa yang Diajar dengan Model Pembelajaran Kooperatif Tipe STAD Berbantuan Media Mistar Geser Bilangan Bulat Dan Media Video Mistar Geser Pada Kelas VII SMP - Alfiah Mutmainnah Ali; Alimuddin; Asdar (Issues in Mathematics Education (IMED), 2019)
This research was conducted to determine the comparison of student learning outcomes through the application of the cooperative model type Student Teams Achievement Divitions assisted by slide rule media and Student Teams Achievement Divitions assisted by slide bar video media. This research was an experimental research involving two groups treated with research sample of 73 students from class VII SMP Sinjaiselected by using the double cluster random sampling technique. Techniques of collecting data using instruments: (1) observation sheet of learning model implementation and (2) tests of mathematics learning result.Data were analyzed with descriptive statistics and inferential statistics with t-test analysis. The results showed that : (1) Average score of mathematics learning outcomes of 37 students after learning using the Student Teams Achievement Divitions assisted by slide rule media model which is 22,22% in the very low category, 22,22% in the medium category, 13,90% in the high category and 19,44% in the very high category. (2) The average score of mathematics learning outcomes from 36 students after learning using the Teams Achievement Divitions assisted by slide bar video media is 18,92% in the very low category, 24,32% in the low category, 40,54% in the medium category 13,52 % in the high and 2,70 % very high categories. (3) There is no significant difference between student learning outcomes after applying the Student Teams Achievement Divitions assisted by slide rule media and Student Teams Achievement Divitions assisted by slide bar video media. in Class VII Junior High School with the material of Addition and Subtraction Round Numbers.